Pandangan dan Peran Organisasi Aisyiyah terhadap Pendidikan di Indonesia Tahun 1914-1923 - Errin Ainun Nisa (Warisan: Journal of History and Cultural Heritage, 2022)
This research is motivated by the establishment of the Muhammadiyah women's organization, Aisyiyah, which is active in education. Aisyiyah was developed to increase the dignity of women to instill a sense of religion so that women can play an active role in education through Islamic da'wah. The method used in this research is the historical method, which consists of four stages: Heuristics, Criticism, Verification, and Historiography. Data collection is done using a literature study. The research results show that the Aisyiyah organization was founded on May 19, 1917, AD. This organization started from the Sopo Tresno recitation association, which K.H Ahmad Dahlan and Siti Walidah founded. Educational views from K.H Ahmad Dahlan and Siti Walidah, who feel that women are significant to get an education. Frobelschool became the first educational institution in Indonesia founded by indigenous people. Through the ABA Kindergarten, which the Aisyiyah Organization pioneered, the Indonesian people have successfully prepared the next generation for an even better future.